Application of method of projective representations to the analysis of exciton-phonon transitions in enantiomorphous tetragonal crystals ZnP₂ and CdP₂ - Koryakov, S.V.; Gubanov, V.O.; Biliy, M.M.; Slobodyanyuk, O.V.; Yanchuk, Z.Z. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The projective representations of the wavevector group were applied to the analysis of exciton-phonon transitions in enantiomorphous tetragonal crystals ZnP₂ and CdP₂. Selection rules for indirect transitions were derived. Using pkrr-method, the different points in the Brillouin zone were examined to identify zero slopes and extremums of the dispersion curves E(k). Photoluminescence and edge absorption polarized spectra were interpreted taking into account the results of above theoretical analysis.